2007
DOI: 10.1093/nar/gkl1112
|View full text |Cite
|
Sign up to set email alerts
|

Ubiquitin-interaction motifs of RAP80 are critical in its regulation of estrogen receptor α

Abstract: In this study, we demonstrate that receptor-associated protein 80 (RAP80) interacts with estrogen receptor alpha (ERα) in an agonist-dependent manner. The interaction is specific for ERα as ERβ and several other nuclear receptors tested did not interact with RAP80. Interaction between RAP80 and ERα was supported by mammalian two-hybrid, GST pull-down, and co-immunoprecipitation analyses. The hinge/ligand-binding domain of ERα is sufficient for interaction with RAP80. RAP80 overexpression reduces ERα polyubiqui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
40
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 54 publications
2
40
1
Order By: Relevance
“…As part of a genome wide search for similar motifs, 5 we found that the region around p53-RE5 as well as p53-RE3 and -4 is surrounded by several putative estrogen response elements. Interestingly, RAP80 has been reported to interact directly with ER␣ and to positively modulate ER␣-mediated transactivation (30). Whether there is any functional link between the interactions of RAP80 with ER␣ and p53 requires further study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…As part of a genome wide search for similar motifs, 5 we found that the region around p53-RE5 as well as p53-RE3 and -4 is surrounded by several putative estrogen response elements. Interestingly, RAP80 has been reported to interact directly with ER␣ and to positively modulate ER␣-mediated transactivation (30). Whether there is any functional link between the interactions of RAP80 with ER␣ and p53 requires further study.…”
Section: Discussionmentioning
confidence: 99%
“…This was stimulated by the observation that RAP80 interacts with estrogen receptor ␣ (ER␣) affecting its stability/ activity (30) and that HDM2, which is regulated by p53, also determines p53 stability. We first examined whether RAP80 and p53 interact.…”
Section: And H1299 Cells (Supplementalmentioning
confidence: 99%
See 2 more Smart Citations
“…Abraxas associates with Rap80 through the N-terminal domain . Rap80 contains two UIM (ubiquitin-interacting motif) domains that have been shown to bind K63-linked ubiquitin chains (Sobhian et al 2007;Yan et al 2007), and are required for the localization of the BRCA1 A complex to ionizing radiation (IR)-induced foci (IRIFs) Sobhian et al 2007;). Abraxas binds BRCC36 through the coiled-coil domains on both proteins .…”
mentioning
confidence: 99%